Forest dynamics and local perceptions of conservation: the case of Bontioli forest in south-western Burkina Faso - Traoré, Mohamed Awalo; Bissonnette, Jean-François; Dossa, Kossivi Fabrice (Frontiers in Forests and Global Change, 2025)
IntroductionThe widespread decline of forests across many countries has prompted governments to implement various measures aimed at conserving forest resources. In the Bontioli Total and Partial Wildlife Reserves, however, effective forest conservation remains a challenge, despite the state’s promotion of participatory management approaches.MethodsThis study employed a diachronic analysis of satellite imagery spanning from 1991 to 2024 to assess land use dynamics, complemented by a qualitative survey involving 150 participants, comprising 26 institutional stakeholders and 124 community members, selected through a combination of random and purposive sampling across four villages. Data were collected through semi-structured interviews and focus group discussions and analyzed using mixed thematic coding (both inductive and deductive) with NVivo 14 software.ResultsSpatial analysis revealed a steady pattern of deforestation, marked by significant agricultural expansion and a reduction in natural vegetation, primarily driven by human activities. Stakeholder perceptions indicated broad awareness of deforestation and its ecological consequences. However, the study also highlighted notable divergences between local communities and authorities in their understanding of concepts such as deforestation and conservation. While community members acknowledged their contribution to environmental degradation, they largely attributed responsibility to external actors and the weakening of traditional authority structures. They also expressed a need for greater institutional recognition and support to align conservation efforts with local development priorities.DiscussionThe study concludes by recommending inclusive governance models grounded in sociocultural values, along with the development of economically viable alternatives to foster stronger community participation in conservation. Nevertheless, as these findings pertain specifically to the Bontioli forest, further research should be conducted in other classified forest areas to support broader and more comparative analyses.